2017
DOI: 10.1021/jacs.7b08831
|View full text |Cite|
|
Sign up to set email alerts
|

Cysteine Linkages Accelerate Electron Flow through Tetra-Heme Protein STC

Abstract: Multi-heme proteins have attracted much attention recently due to their prominent role in mediating extracellular electron transport (ET), but one of their key fundamental properties, the rate constants for ET between the constituent heme groups, have so far evaded experimental determination. Here we report the set of heme-heme theoretical ET rate constants that define electron flow in the tetra-heme protein STC by combining a novel projector-operator diabatization approach for electronic coupling calculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(94 citation statements)
references
References 31 publications
7
87
0
Order By: Relevance
“…Stacking arrangements of aromatic rings generally prefer parallel (offset face-to-face) or perpendicular (T-shaped) conformations (Janiak, 2000). The parallel stacking yields the highest electronic coupling, which maximizes electron transfer (Jiang et al, 2017), whereas the T-shape enhances structural stability (Janiak, 2000). Hemes in the OmcS nanowires form parallel-stacked pairs, with each pair perpendicular to the next, forming a continuous chain over the entire length of the filament ( Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Stacking arrangements of aromatic rings generally prefer parallel (offset face-to-face) or perpendicular (T-shaped) conformations (Janiak, 2000). The parallel stacking yields the highest electronic coupling, which maximizes electron transfer (Jiang et al, 2017), whereas the T-shape enhances structural stability (Janiak, 2000). Hemes in the OmcS nanowires form parallel-stacked pairs, with each pair perpendicular to the next, forming a continuous chain over the entire length of the filament ( Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the photoreduction time courses should reflect interplay of the site of electron injection and the rate(s) of subsequent electron distribution along the heme chain. Experiments and computational chemistry have shown that inter‐heme electron transfer within STC occurs at rates >10 4 s −1 and so on a timescale much faster than STC cumulative photoreduction. In these circumstances heme E M values will define the distribution of photo‐accumulated electrons across the heme chain.…”
Section: Resultsmentioning
confidence: 99%
“…We consider there to be much scope for engineering these proteins, and homologues, to achieve diverse and bespoke electrical properties. For example, longer‐lived charge separation and faster electron migration from the site of photoenergised electron injection might be achieved by an optimal redox landscape in the heme chain and/or injection into heme with its porphyrin ring parallel, rather than perpendicular, to its neighbour . Furthermore, the 2D and 3D heme arrays of larger multiheme cytochromes might display additional functionalities: providing light‐driven molecular junction boxes, for example.…”
Section: Resultsmentioning
confidence: 99%
“…I note that the absence of heme-heme ET on this time scale is in line with latest computational predictions for the electron flux across a similar protein from S. Oneidensis, STC, estimated to be in the order of 10 7 s −1 . 29 Hence, an extension of the measurements of Ref. 22 to the microsecond regime would be instructive to verify some of the predictions of recent computations.…”
Section: Electron Transfer Kineticsmentioning
confidence: 82%
“…Then I place focus on experimental measurements of electronic properties of single MHCs [22][23][24] and their complexes (nm length scale) 15 as well as their interpretation by theory and computation. [24][25][26][27][28][29][30][31] In this respect I distinguish between electron transfer (ET) and electron transport (ETp) measurements. In ET an electron transfers between an electron donor and an electron acceptor resulting in a change of their net charge, which is accompanied by dielectric relaxation of the environment if present.…”
Section: Introductionmentioning
confidence: 99%